The Effectiveness of Instagram Visual Campaigns on Brand Awareness Among Gen Z - Lamriama Valintina Chrystina Siregar; Syafrizal Helmi Situmorang; Baby Karina Fawzeea Sembiring (International Journal of Economics and Management Sciences, 2025)
This study discusses the role of social media in enhancing brand awareness among Generation Z (Gen Z), a group known for their digital savvy and high reliance on technology. Gen Z, born between 1997 and 2012, are highly connected consumers on social media platforms such as Instagram, TikTok , and YouTube . Social media has become a major channel for building and increasing brand awareness due to its ability to reach a wide audience , interact directly, and provide a personalized experience. Through a literature review, this article identifies factors that influence the effectiveness of social media in increasing brand awareness. awareness , including choosing the right platform, relevant and engaging content, and user engagement. In addition, the study also discusses the challenges that brands face in building awareness among Gen Z, such as information overload and the tendency of audiences to be more critical of advertising. The results of this review can provide insights for marketers in designing more effective social media strategies for the younger generation and help brands stay relevant in an increasingly competitive market.